The bees of the genus Hylaeus Fabricius 1793 of the Asian part of Russia, with a key to species (Hymenoptera: Apoidea: Colletidae) - Proshchalykin, Maxim Yu.; Dathe, Holger H. (Zootaxa, 2012)
Thirty-one species of the bee genus Hylaeus are recorded from the Asian part of Russia. Three species: Hylaeusdolichocephalus Morawitz 1876, H. altaicus Dathe 1986, and H. telmenicus Dathe 1986 are recorded for the first timefrom Russia, and H. angustatus (Schenck 1861) is newly recorded from the Asian part of Russia. Based on type study,new synonymy has been established for Hylaeus stentoriscapus Dathe 1986 = Hylaeus pallescens Cockerell 1924, syn.nov.; Hylaeus atromicans Cockerell 1924 and Hylaeus sinicola Cockerell 1924 = Hylaeus rinki (Gorski 1852), syn. nov.;Hylaeus monostictus Cockerell 1924 = Hylaeus concinnus Cockerell 1924, syn. nov.; Hylaeus nigrocuneatus var.rufipennis Cockerell 1924, Hylaeus brevicuneatus Cockerell 1924, Hylaeus lavrushini Cockerell 1924, and Hylaeusparadifformis Ikudome 1989 = Hylaeus nigrocuneatus Cockerell 1924, syn. nov.; Prosopis transversalis Gussakovskij1932 and Prosopis sericata Warncke 1972 = Hylaeus transversalis Cockerell 1924, syn. nov.; Prosopis heliaca Warncke1992 = Hylaeus dolichocephalus Morawitz 1876, syn. nov.; Prosopis chasanensis Romankova 1995 = Hylaeusaborigensis Dathe 1994, syn. nov.; Hylaeus chasanensis negoroi Ikudome 2004 = Hylaeus aborigensis negoroi Ikudome2004, syn. nov.; Hylaeus monticola Bridwell 1919 = Hylaeus confusus Nylander 1852, syn. nov. The subgenera PatagiataBlüthgen 1949, stat. resurr. and Nesohylaeus Ikudome 1989, stat. resurr. are reinstated. Illustrated keys to the males and females of all species known from the Asian part of Russia are provided.